Kiki – A Virtual AI Desktop Aider - P, Nisarga; R, Sunitha; C, Pavithra H; K, Yashashwini Pai (Journal of Electronics and Informatics, 2024)
The research“Kiki” is a voice-controlled virtual desktop assistant designed to enhance user productivity and streamline interaction with desktop environments. Leveraging natural language processing (NLP) techniques, Kiki enables users to perform various tasks through voice commands, ranging from opening applications to searching the web and playing music. The system employs state-of-the-art language models to understand user queries and generate contextually relevant responses, providing a seamless and personalized user experience. Key functionalities include task automation, information retrieval, and web search, allowing users to execute commands efficiently and effortlessly. By combining advanced NLP capabilities with intuitive voice interaction, Kiki represents a significant advancement in desktop assistant technology, promising to reshape the way individuals interact with their computers.
Keywords: Desktop Assistant; Voice Interface; Natural Language Understanding; Task Automation; Conversational AI; Personal Virtual Assistant; Voice Command Recognition